Causes and Effects of Variation Orders in Water Supply Projects in Nepal - Kandel, Birendra (Prashasan: The Nepalese Journal of Public Administration, 2025)
In Nepal's construction industry, variation orders remain a major concern. They are inevitable in nearly every construction project and carry significant implications for project outcomes. If not managed properly, variation orders can negatively impact cost, schedule, and quality. This study examines the causes and effects of variation orders in water supply projects in Nepal. The research is based on a review of variation order documents from 19 water supply projects and a questionnaire survey involving clients, consultants, and contractors. A total of 52 participants contributed to the study. Data were analyzed using the Likert Scale, Relative Importance Index (RII), and Severity Index (SI). The five major causes identified are: (i) design changes during implementation, (ii) inadequate site investigation during project preparation, (iii) inaccurate cost estimation by consultants, (iv) additional work demands from user committees/beneficiaries, and (v) unforeseen site conditions, with RII values of 0.862, 0.858, 0.854, 0.838, and 0.835, respectively. The primary effects identified include cost overruns, time overruns, and increased overhead expenses.